2015
DOI: 10.1158/1535-7163.mct-14-0833
|View full text |Cite
|
Sign up to set email alerts
|

The Selective PI3K Inhibitor XL147 (SAR245408) Inhibits Tumor Growth and Survival and Potentiates the Activity of Chemotherapeutic Agents in Preclinical Tumor Models

Abstract: Dysregulation of PI3K/PTEN pathway components, resulting in hyperactivated PI3K signaling, is frequently observed in various cancers and correlates with tumor growth and survival. Resistance to a variety of anticancer therapies, including receptor tyrosine kinase (RTK) inhibitors and chemotherapeutic agents, has been attributed to the absence or attenuation of downregulating signals along the PI3K/PTEN pathway. Thus, PI3K inhibitors have therapeutic potential as single agents and in combination with other ther… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 27 publications
1
35
0
Order By: Relevance
“…Furthermore, 50 mg/kg WX-037 generated a tumour growth delay in HCT116 colorectal tumour xenograft models, which is consistent with previous unpublished studies using WX-037 and published studies using other pan class I PI3K inhibitors that reported tumour growth delay, or in some cases tumour stasis, with greater sensitivity in PIK3CA mutant or PTEN null cells and tumours [5, 14, 15, 4651]. Pharmacokinetic studies indicated that concentrations of WX-037 in plasma and tumour tissue increased dose dependently and that WX-037 tumour and plasma levels generally exceeded the in vitro GI 50 concentration at an early time point (6 h), depending on the cell line and dose, whereas levels generally had decreased below the GI 50 value by the later time point (24 h).…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, 50 mg/kg WX-037 generated a tumour growth delay in HCT116 colorectal tumour xenograft models, which is consistent with previous unpublished studies using WX-037 and published studies using other pan class I PI3K inhibitors that reported tumour growth delay, or in some cases tumour stasis, with greater sensitivity in PIK3CA mutant or PTEN null cells and tumours [5, 14, 15, 4651]. Pharmacokinetic studies indicated that concentrations of WX-037 in plasma and tumour tissue increased dose dependently and that WX-037 tumour and plasma levels generally exceeded the in vitro GI 50 concentration at an early time point (6 h), depending on the cell line and dose, whereas levels generally had decreased below the GI 50 value by the later time point (24 h).…”
Section: Discussionsupporting
confidence: 89%
“…Pilaralisib (XL147, SAR245408) is an orally bioavailable and reversible pan-class I A PI3K inhibitor against p110α/δ/γ with IC 50 of approximate 30 nM, but less potent upon p110β [43]. Apart from GBM, it exhibits dose-dependent anti-proliferative effects on breast cancer cells through inhibition on PI3K and Akt activation [44].…”
Section: Introductionmentioning
confidence: 99%
“…36), which has shown activity in preclinical tumor models and in patients with solid tumors (36)(37)(38). In the phase I safety, pharmacokinetic (PK) and pharmacodynamic study in patients with solid tumors, the maximum tolerated dose (MTD) and recommended phase II dose of the pilaralisib capsule formation was 600 mg administered orally with continuous once-daily dosing (37).…”
Section: Introductionmentioning
confidence: 99%